1995
DOI: 10.1149/1.2044049
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism of Electroless Metal Deposition Using ZnO Thin Film (I): Process of Catalyst Formation

Abstract: The reaction mechanism of electroless metal deposition proceeding selectively on a ZnO thin film coated on a glass substrate was investigated by x-ray diffraction, x-ray photoelectron spectroscopy, and inductively coupled plasma measurements. The ZnO thin film was activated for e]ectroless metal deposition just by immersion in i.I mM PdC]2 solution adjusted to pH 2.5. In this process, Pd(II) was selectively adsorbed on the ZnO thin film while simultaneously the ZnO underwent dissolution. The dissolution of ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…The ZnO nanorod arrays rooted in the substrate were washed with distilled water several times, and dried at 60 uC. The synthesis of Pd/ZnO NRs was performed through immersion of ZnO NRs into the palladium chloride-ethanol solution at room temperature under an ultraviolet lamp (365 nm, around 5.3 mW cm 22 ) irradiation for 30 min. A palladium precursor solution with a light yellow color was obtained by dissolving 0.75 mM PdCl 2 in anhydrous ethanol with vigorous stirring for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ZnO nanorod arrays rooted in the substrate were washed with distilled water several times, and dried at 60 uC. The synthesis of Pd/ZnO NRs was performed through immersion of ZnO NRs into the palladium chloride-ethanol solution at room temperature under an ultraviolet lamp (365 nm, around 5.3 mW cm 22 ) irradiation for 30 min. A palladium precursor solution with a light yellow color was obtained by dissolving 0.75 mM PdCl 2 in anhydrous ethanol with vigorous stirring for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…21 Accordingly, the zinc atoms become quite easy to dissociate from the ZnO lattice, which causes the dissolution seen in the present system. 22 The remaining surface oxygen atoms attract the palladium ions in bulk solution by electrostatic interaction, and the Pd(II) ions are then adsorbed on the ZnO surface and subsequently reduced to metallic palladium by photochemical reduction. Actually, the photocatalytic activities of ZnO-based materials are well known, and which have also been used to reduce Pd(II) ions acting as active sites for the electroless plating of copper on patterned areas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…due to its high catalytic activity for a breadth of chemical reactions, such as hydrogen evolution reaction 2 and methane oxidation. 3 In addition, Pd is capable of activating the non-active surface prior to the autocatalytic electroless deposition of Ni, Cu, 4 Co and Pd.…”
mentioning
confidence: 99%
“…Preparation of Cu layer in aqueous solutions showed several advantages over the above mentioned techniques. Yoshiki et al 1 and Sun et al 2 reported a chemical method for preparing Cu layer on ZnO film. The method consisted of three steps; (i) adsorption of Pd 2+ ions on the ZnO surface by immersing the film in an acidic PdCl 2 solution, (ii) formation of Pd (0) layer by photoreduction of the Pd 2+ ions using UV irradiation, and (iii) electroless Cu plating on the Pd (0) layer.…”
mentioning
confidence: 99%